Effects of soy beverage and soy-based formula on growth, weight, and fecal moisture: experimental study in rats - Maisa de Lima Correia Silva; Patrícia da Graça Leite Speridião; Renata Marciano; Olga Maria S. Amâncio; Tânia Beninga de Morais; Mauro Batista de Morais (Elsevier, 2015)
OBJECTIVE: To compare body growth, weight, and fecal moisture in recently weaned rats fed exclusively on infant soy formula and soy-based beverage. METHODS: Three similar groups were formed (n = 10/group) consisting of weanling Wistar rats, maintained in metabolic cages. One group was fed soy protein-based beverage, another with soy-based infant formula, and another with cow's milk infant formula (control group). Water and diet were offered ad libitum. Body weight and length were measured. Stool was collected for three consecutive days. RESULTS: Weight and length were lower (p = 0.001; p = 0.001) in the groups receiving soy protein-based beverage (73.16 ± 5.74 g; 23.94 ± 1.04 cm) and soy-based formula (71.11 ± 5.84 g; 24.74 ± 0.60 cm) in relation to the group receiving cow's milk formula (84.88 ± 9.75 g; 26.01 ± 0.91 cm). Fresh fecal weight was greater (p < 0.001) in the soy-based beverage (3.44 ± 0.48 g) than in the soy-based formula (0.79 ± 0.20 g) and cow's milk-based formula (0.42 ± 0.17 g). Fecal moisture was higher (p < 0.001) in the group receiving soy protein-based beverage (47.28 ± 9.02%) and soy-based formula (37.21 ± 13.20%) than in the group receiving cow's milk formula (22.71 ± 10.86%). CONCLUSION: The growth of rats fed soy protein-based beverage and soy-based formula was lower than those fed cow's milk-based formula. The soy protein-based beverage resulted in significant increase in fecal weight and moisture.